Liberia : Report on Post-Conflict Economic Situation and Prospects for January-June 2004. (IMF Staff Country Reports; Country Report ;, 2004)
Intermittent civil wars have largely destroyed Liberia's physical and economic structures and the government's capacity to devise and implement policies. Executive Directors expressed concern about the weak revenue performance, lack of progress on fiscal transparency, and accountability. They emphasized the need to accelerate structural reforms, welcomed the National Transitional Government of Liberia's resumption of regular token monthly payments to the IMF, and suggested that continued cooperation with the IMF and implementation of sound policies will facilitate the development of a Staff-Monitored Program.